Analisis Risiko Logam Berat Cr dan Cu Pada DAS Cilamaya - Sopian, Sabiha Mawaddah; Cahyani, Intan; Manenti, Dini Auliana; Alifiana, Winanda; Listriyani, Ayu Suranti (Jurusan Kesehatan Lingkungan Poltekkes Kemenkes Padang, 2023)
The existence of human activities around the watershed can cause polluted water, one of the pollutant substances is heavy metals. The purpose of this study was to measure the concentration and analyze the risk of exposure to metals contained in river water. This research was conducted in the Cilamaya River, West Java Province. Sampling was carried out 3 times in March, June and October 2021 at 4 different sampling points. The data used is secondary data from the Department of Environment and Forestry of West Java Province and then calculated and analyzed using the equation formula. The results of this study indicate that the risk of Cr heavy metal contamination at points 1-4 is 0.010958904. Meanwhile, the risk of Cu heavy metal contamination at point 1-4 is 0.0109589. Then the risk value for both Cu and Cr metals is ≤ 1, which means that the Cilamaya watershed is not at risk.